Analytics to monitor local impact of the Protecting Access to Medicare Act's imaging clinical decision support requirements. (5th August 2022) - Valtchinov, Vladimir I; Murphy, Shawn N; Lacson, Ronilda; Ikonomov, Nikolay; Zhai, Bingxue K; Andriole, Katherine; Rousseau, Justin; Hanson, Dick; Kohane, Isaac S; Khorasani, Ramin
Abstract: Objective: This study aimed is to: (1) extend the Integrating the Biology and the Bedside (i2b2) data and application models to include medical imaging appropriate use criteria, enabling it to serve as a platform to monitor local impact of the Protecting Access to Medicare Act's (PAMA) imaging clinical decision support (CDS) requirements, and (2) validate the i2b2 extension using data from the Medicare Imaging Demonstration (MID) CDS implementation. Materials and Methods: This study provided a reference implementation and assessed its validity and reliability using data from the MID, the federal government's predecessor to PAMA's imaging CDS program. The Star Schema was extended to describe the interactions of imaging ordering providers with the CDS. New ontologies were added to enable mapping medical imaging appropriateness data to i2b2 schema. z -Ratio for testing the significance of the difference between 2 independent proportions was utilized. Results: The reference implementation used 26 327 orders for imaging examinations which were persisted to the modified i2b2 schema. As an illustration of the analytical capabilities of the Web Client, we report that 331/1192 or 28.1% of imaging orders were deemed appropriate by the CDS system at the end of the intervention period (September 2013), an increase from 162/1223 or 13.2% for the first month of the baseline period, December 2011 ( P = .0212), consistent with previous studies. Conclusions: The i2b2 platform can be extended to monitor local impact of PAMA's appropriateness of imaging ordering CDS requirements.